PREPARASI NANOPARTIKEL OKSIDA BESI BERBASIS PASIR ALAM LOGAS DIDOPING KOBALT SEBAGAI MATERIAL LINGKUNGAN - Erwin Amiruddin; Amir Awaluddin; Muhammad Rizki (Indonesian Physics Communication, 2023)
The  cobalt  doped  iron oxide  nanoparticles  have  been  prepared  by  ball  milling  method  using  Logas natural sand as a raw material. The milled iron oxide nanoparticles were doped using cobalt with concentration of 0, 5, 10, 15,  and  20  wt.%.  The  structural, magnetic and  optical properties  were  studied  using  X-ray diffractometer (XRD), vibration sample magnetometer (VSM), and UV-Vis  spectroscopy, respectively. The samples  show  cobalt-hematite  nanoparticles  as  indicated  through  XRD  measurement.  The  XRD measurements  confirmed  the  formation  of  crystalline,  rhombohedral  crystal  structure  and  hematite  nanoparticles.    The  average  crystallite  size calculated using Scherrer formula found to be 38.51, 35.67, 33.75, 32.73, and 31.53 nm after being doped with cobalt 0, 5, 10,  15,  and  20  wt. %,  respectively. The samples  exhibited  weak  ferromagnetic  behaviour  with  the  coercivity  ranged from  124  Oe  to 299  Oe.  The optical properties strongly depend on cobalt  content  and  showed  that  the  band  gaps  of  cobalt  doped  hematite  decrease  with  increasing  cobalt  content.  This work suggests that the prepared iron oxide nanoparticles are attractive photo Fenton catalysts for the degradation of methylene blue in the water.